The Influence of Unmanned Aerial Vehicle Wind Field on the Pesticide Droplet Deposition and Control Effect in Cotton Fields - Haoran Li; Ying Li; Muhammad Zeeshan; Longfei Yang; Zhishuo Gao; Yuting Yang; Guoqiang Zhang; Chunjuan Wang; Xiaoqiang Han (Agronomy)
Unmanned aerial vehicles (UAVs) offer significant advantages in agricultural pest control. The present study investigated the influence of rotor-induced wind fields from multirotor UAVs (six-rotor T30, eight-rotor T40, eight-rotor T50, and four-rotor T60) on pesticide droplet deposition and control efficacy in cotton fields. The results revealed that UAVs with stronger wind fields (e.g., T60) significantly improved droplet deposition in the middle and lower canopy layers, with penetration rates of 54.09–56.04% which were notably higher than the penetration rate observed for the T30 (45.83–44.76%). UAVs exhibited a pesticide utilization efficiency of 75.47–77.86% indicating a 32.2% improvement over the boom sprayers, which achieved a utilization efficiency of 58.88%. While the boom sprayers initially showed a better pest control efficacy, the efficacy gap narrowed after 7 days, with T40 achieving 91.55%, comparable to the efficacy of boom sprayers (93.36%). Following a second spraying, UAVs achieved defoliation rates exceeding 93% and boll opening rates exceeding 90%, similar to that of boom sprayers. This study underscores the critical role of wind field intensity in influencing the spraying performance, with UAVs featuring stronger wind fields exhibiting superior droplet penetration and distribution uniformity. These findings provide valuable scientific insights for optimizing UAV spraying in cotton fields.